Ketidakpuasan Terhadap Tubuh Yang Menghasilkan Obsesi Pada Penampilan Ideal Dikalangan Mahasiswa - Zata Ismah; Dianti Ria Saputri; Riska Herlinda; Nur Afni Fitria; Fatimah Anjelica (Journal of Communication and Social Sciences, 2024)
As is common nowadays, many students pay more attention to their pay more attention to his figure in order to have a good figure amongst them. Having a thin body, tall, white and not fat is a characteristic of good appearance among students, so that those who are dissatisfied with their bodies are interested in achieving good looks. According to Sejcova (2008), body dissatisfaction is a negative body negative opinion of the body that arises when a person's body image does not match the body image standards of others. While good looks is a series of activities that make a person confident and become a brilliant person from within, as well as a well-maintained physical appearance. physical appearance that is always maintained. This study aims to find out how body dissatisfaction can affect the mind to look good among college students by using quantitative method by collecting data from using a quantitative method by collecting data from questionnaires that were subjected to college students from UIN Raden Fatah Palembang, totaling 133 respondents. Raden Fatah Palembang which amounted to 133 respondents. This research using 2 scales, namely the body image scale of 9 items and the image complexity scale of 21 items. image complexity scale of 21 items.